Olympic medals, economy, geography and politics from Sydney to Rio - Grancay, M.; Dudas, T. (Iranian Economic Review, 2018)
The paper uses Heckman model to examine the statistical importance of over 140 independent variables on the Olympic performance of all countries participating in the Summer Olympic Games from Sydney 2000 to Rio 2016. We find that countries which export more products have a higher likelihood of winning an Olympic medal than their counterparts exporting fewer products, and explain why this is the case. Statistical importance of gross domestic product per capita, labor force, average temperature and three host effects (previous host, current host, future host) is also confirmed while the role of political variables in Olympic success remains inconclusive.